The role of integrated mental and community physical healthcare trusts in responding to the COVID-19 pandemic in the UK. (June 2021) - Tracy, Derek; Forrest, Anna; Underwood, Benjamin R.
Summary: For several decades, mental health services within the UK's National Health Service were provided by specialist mental health trusts. More recently many of these trusts have integrated community physical health services into their operations. We describe here how two integrated mental health trusts in England were able to make an enhanced response to the COVID-19 pandemic.